Novos dados para o estudo dos Chões de Alpompé – Santarém - Pimenta, João; Arruda, Ana Margarida (Estudos Arqueológicos de Oeiras, 2014)
Chões de Alpompé was recognized as an archaeological site only during the 50´s, the time from which it was extensively and intensively surveyed, in several times and in several contexts. The artifacts gathered during those fieldworks where frequently published, stating the existence of an important roman republican occupation which was early associated with Decimus Junius Brutus military campaign, in 138 BC. The same association also allowed its match to Strabo´s Moron, considering the existence of some artifacts that indicated an Orientalizing Iron Age affiliation. A collection of unpublished materials that remained deposited in Casa dos Patudos (Alpiarça) since the 70´s deserved a proper analyzes, enabling an overall characterization of the site that take into account the available data.